PERAN DINAS KOPERASI DAN USAHA MIKRO DALAM PENANGANAN DAMPAK COVID-19 BAGI UMKM KOTA BATAM - Syavitri, Novi; Salsabila, Lubna (SCIENTIA JOURNAL, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are community-based business activities that can increase income and economic equity of the community. Although it’s a strong sector, in fact, MSMEs cannot be separated from the impact of the Covid-19 pandemic. Through the Department of Cooperatives and micro enterprises, it takes the role of the government in carrying out economic recovery again through MSME activities that have been slowed down due to exposure to the Covid-19 pandemic. The purpose of this research is to find out the role of the Cooperative and Microenterprise office in handling the impact of Covid-19 for Batam city MSMEs, so that MSME activities can recover and rise again in the midst of the Covid-19 pandemic or the current post-pandemic. In this research, researchers used qualitative methods with descriptive approach. In handling the impact of Covid-19 for MSMEs, the Batam City Cooperative and Microenterprise Office plays a role in three things, namely as a regulator, facilitator, and catalyst. In all three roles, the Department of Cooperatives and micro enterprises Batam city has performed its role well. However, there are some factors that affect the Department of Cooperatives and Microenterprises in handling the impact of Covid-19 for Batam city MSMEs.